EXISTENCE AND CHARACTERISTICS OF SOLE PROPRIETORSHIP IN INDONESIA - Aliza Madina Putri; Paramita Prananingtyas (Diponegoro Law Review, 2022)
Sole proprietorship is the simplest business form and most used for Micro, Small and Medium Enterprises that has been dominating Indonesia’s economy. Sole proprietorship wasn’t a legal entity, therefore it has an unlimited liability. This become a consideration for entrepreneurs when they start a business. The issue discussed the existence and characteristics of sole proprietorship in Indonesia after Law 11/2020. This is a normative juridical research through a statutory and conceptual approach. The purpose of this research is to explain the characteristic of sole proprietorship in Indonesia and compares it with other Asian countries. The result indicates that sole proprietorship based on Law 11/2020 is a new legal entity as the concept expansion of Limited Liability Company with a limited liability that meets the criteria of micro and small business. It provides legality for entrepreneurs and a facility to access sources of funding. The regulation that determines sole proprietorship as a legal entity is only adopted by few countries like India.